Censorship detected in BH (Bahrain) - Voidly (2026)
CRITICAL severity censorship detected in Bahrain. Confidence: 90%. Data sourced from OONI.
Censorship Incident ID: BH-2026-0319
Keywords: censorship; BH; censorship; critical